Design and Development of a Virtual Instrument for Hazardous Environment Monitoring and Control Using Lab VIEW. Issue 1 (2nd January 2016) - Sureshkumar, A.; Muruganand, S.; Balakrishnan, P.
Abstract: The increased high performance of personal computers and their reduced cost has made it possible for the development of computer based monitoring and control systems. Industry needs several measurement systems that can measure safety risk parameters of the hazardous area. Although wireless sensor networks have been widely used, combining virtual instrument technology to achieve the purpose of safety measurement has several benefits. These systems are efficient and cost-effective for acquiring and analyzing sensor signals. Utilizing virtual instrumentation to achieve safety measurement will largely decrease the cost and increase the flexibility of the instruments. This work aims at designing a virtual instrument for acquiring and processing of hazardous parameter signal. The software platform in terms of virtual instruments is developed under Lab VIEW programming environment and integrated with computer controlled system.